PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI IMPLEMENTASI METODE PEMBELAJARAN COOPERATIVE LEARNING TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS XII SMA NEGERI 1 PUNGGUR - Noto Margianto (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This study aims to improve student learning outcomes through the implementation of cooperative learning method of Cooperative Integrated Reading and Composition (CIRC) type. This type of research is CAR (Classroom Action Research). The subject of the recipients of the action is the students of grade XII IPA 4 Senior High School 1 Punggur, amounting to 33 students. Data collection methods used are observation method, test method, documentation method and field note. Data analysis technique used are data analysis process, data presentation, and data verification. To guarantee the validity of data used triangulation technique. The result of the research shows the improvement of mathematics learning outcomes of students on Logarithmic subject. This can be seen from: 1) Student's completeness before the action is 14 students (39,13%) and at the end of action reaches 19 students (82,61%), 2) The courage of student to ask unclear material before action that is 5 Students (21.74%) and at the end of the action reached 15 students (65.22%), 3) Students who responses to other students' opinions before action is2 students (8.69%) and at the end of the action reaches 11 students (47 , 82%), 4) Enthusiastic students to do the problem before the action that is 8 students (34,78%) and at the end of action reaches 17 students (73,91%). The conclusion of this research is the implementation of cooperative learning method type Cooperative Integrated Reading and Composition (CIRC) can improve student learning achievement of mathematics on Logarithmic subject.